Effects of Participation Barriers on Consumption Desire and Participation Intention in Taekwondo among Chinese Youth - Hebin Chong; 박순문 (International Journal of Advanced Culture Technology(IJACT), 2025)
The purpose of this study is to examine the effects of participation barriers on consumption desire and participation intention in Taekwondo among Chinese youth. To achieve this objective, the study targeted Chinese adolescents currently practicing Taekwondo. A total of 400 survey responses were collected using a convenience sampling method via an online platform. After excluding 50 responses due to insincerity or duplicate entries, data from 350 participants (200 males and 150 females) were used for final analysis. The survey instrument was a questionnaire based on previously validated and reliable scales from prior studies, which were modified and supplemented to fit the context of this research. The questionnaire employed a 5- point Likert scale. The collected data were analyzed using SPSS version 22.0, and statistical methods appropriate for the research objectives were applied. The results derived through this process are as follows.: First, Taekwondo participation barriers were found to partially influence consumption desire. Second, Taekwondo participation barriers were also found to partially affect participation intention. Third, Taekwondo consumption desires were partially influential on participation intention.